An ultra-high vacuum electrochemical/mass spectrometry study of anodic decomposition of a protic ionic liquid - Goodwin, Sean; Gibson, Joshua; Jones, Robert; Walsh, Darren A. (Elsevier, 2018)
Protic ionic liquids (PILs) are ionic liquids that are formed by proton transfer from Brønsted acids to Brønsted bases, and which are being proposed for use in a wide range of electrochemical devices. In this contribution, we describe electrolysis of the PIL diethylmethylammonium trifluoromethanesulfonate at Pd, Pt, and Au electrodes in an ultra- high vacuum chamber connected to a mass spectrometer. At potentials negative of about −0.8 V vs. Pd/H, reduction of the PIL cations occurs, liberating H2. Positive of about 2.2 V vs. Pd/H, electrooxidation of the PIL anions occurs, resulting in the detection of a number of fragments of the trifluoromethanesulfonate ions using the mass spectrometer. Notably, electrooxidation of the PIL anions occurs at the same potential, regardless of whether Pt, Au, or Pd is used as the electrode. In contrast, electrooxidation of water in the PIL occurs at different potentials in the PIL as the electrode composition changes. These results show that the electrochemical window of the PIL is independent of the electrode composition, but if water is present in the liquid, this independence is masked by the electrolysis of water.